Use of In Vitro Transcription System for Analysis of Corynebacterium glutamicum Promoters Recognized by Two Sigma Factors - Šilar, Radoslav; Holátko, Jiří; Rucká, Lenka; Rapoport, Andrey; Dostálová, Hana; Kadeřábková, Pavla; Nešvera, Jan; Pátek, Miroslav (Current microbiology, 2016)
Promoter activities in Corynebacterium glutamicum strains with deletions of genes encoding sigma factors of RNA polymerase suggested that transcription from some promoters is controlled by two sigma factors. To prove that different sigma factors are involved in the recognition of selected Corynebacterium glutamicum promoters, in vitro transcription system was applied. It was found that a typical housekeeping promoter Pper interacts with the alternative sigma factor σ(B) in addition to the primary sigma factor σ(A). On the other way round, the σ(B)-dependent promoter of the pqo gene that is expressed mainly in the stationary growth phase was active also with σ(A). Some promoters of genes involved in stress responses (P1clgR, P2dnaK, and P2dnaJ2) were found to be recognized by two stress-responding sigma factors, σ(H) and σ(E). In vitro transcription system thus proved to be a useful direct technique for demonstrating the overlap of different sigma factors in recognition of individual promoters in C. glutamicum.
Keywords: Gene Expression Regulation, Bacterial; Bacterial Proteins; promotorové oblasti (genetika); Corynebacterium glutamicum; Promoter Regions, Genetic; Sigma Factor; sigma faktor; bakteriální proteiny; Transcription, Genetic; genetická transkripce; regulace genové exprese u bakterií